PAPER–BASED ZnO, ZnO:SnO2 AND SnO2 ULTRAVIOLET SENSORS - Reem Saadi Khaleel; Salah Kaduri Haza’a (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2015)
Three photoelectrical devices ZnO, ZnO:SnO2 and SnO2 are made on common pencil drawn circuit over a regular paper as substrate. These three sensors are well capable of detecting UV light and demonstrate features comparable to those of made with complex and expensive techniques. The responses of these sensors are different to the two UV spectra which are used as light sources. Explanation of sensors responses relates samples energy gap values with the UV wavelengths energies and intensities of the two applied UV spectra. Also the role of oxygen adsorption on the variations of samples resistances is discussed. Measurements comparing properties of the three sensors show better performance for ZnO sensor than the two other sensors; but with longer rise and fall times.